2014
DOI: 10.1101/gad.241950.114
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin-associated interactions of Drosophila HP1a with dADD1, HIPP1, and repetitive RNAs

Abstract: Heterochromatin protein 1 (HP1a) has conserved roles in gene silencing and heterochromatin and is also implicated in transcription, DNA replication, and repair. Here we identify chromatin-associated protein and RNA interactions of HP1a by BioTAP-XL mass spectrometry and sequencing from Drosophila S2 cells, embryos, larvae, and adults. Our results reveal an extensive list of known and novel HP1a-interacting proteins, of which we selected three for validation. A strong novel interactor, dADD1 (Drosophila ADD1) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
150
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 75 publications
10
150
1
1
Order By: Relevance
“…15 The crosslinking-coupled tandem affinity purification strategy not only improves preservation of bait protein-protein interactions, but also allows the analysis of target DNA in parallel. [16][17][18] We found that Sex comb on midleg (Scm), previously known as a substoichiometric component of PRC1, 3,19 is the only protein strongly enriched with both complexes. 15 Surprisingly, we also found through BioTAP-XL DNA sequencing that Pc, E(z) and Scm show a broad distribution on silent chromatin and overlap significantly with the broad domains of H3K27me3, though they also still show sharp peaks on PREs.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…15 The crosslinking-coupled tandem affinity purification strategy not only improves preservation of bait protein-protein interactions, but also allows the analysis of target DNA in parallel. [16][17][18] We found that Sex comb on midleg (Scm), previously known as a substoichiometric component of PRC1, 3,19 is the only protein strongly enriched with both complexes. 15 Surprisingly, we also found through BioTAP-XL DNA sequencing that Pc, E(z) and Scm show a broad distribution on silent chromatin and overlap significantly with the broad domains of H3K27me3, though they also still show sharp peaks on PREs.…”
mentioning
confidence: 96%
“…This demonstrates that BioTAP-XL profiles reflect the distribution of each specific bait protein, rather than any shared affinity of the epitope tag. 17 To probe the colocalization pattern of H3K27me3 and Polycomb proteins with respect to topologically associating domains (TADs) genome-wide, we compared the enrichment of H3K27me3 and Polycomb proteins around the topological boundaries from Hi-C data in embryos ( Fig. 2A).…”
mentioning
confidence: 99%
“…Previously, our group identified MSL3 associated proteins using large-scale amounts (5). To determine the proteins enriched by the pulldown, we first normalized the total peptide counts for each protein (Dataset S1) to the protein length and to the total number of peptides identified across all proteins in the LC-MS experiment (10) before comparing the pulldown with the input.…”
Section: Resultsmentioning
confidence: 99%
“…In each case, previously known protein subunits as well as novel, yet functionally relevant interactors were identified (Alekseyenko et al, 2014a, Alekseyenko et al, 2014b). Similarly, the DNA targeting of the tagged bait was resolved, and agreed strongly with previous experiments.…”
Section: Commentarymentioning
confidence: 99%